Climate-driven trends of biogenic volatile organic compound emissions and their impacts on summertime ozone and secondary organic aerosol in China in the 2050s. (1st December 2019) - Liu, Song; Xing, Jia; Zhang, Hongliang; Ding, Dian; Zhang, Fenfen; Zhao, Bin; Sahu, Shovan Kumar; Wang, Shuxiao
Abstract: As a precursor of ozone (O3 ) and secondary organic aerosol (SOA), volatile organic compounds (VOCs) largely derive from natural sources, which may vary with future climate change patterns. In this study, the emissions and impacts of biogenic VOCs (BVOCs) were projected into summertime of the 2050s (average for 2048–2052) for China using the Model of Emissions of Gases and Aerosols from Nature (MEGAN) and the Community Multiscale Air Quality Model (CMAQ) driven by future meteorological fields simulated with the Weather Research and Forecasting Model (WRF) for two future climate scenarios (RCP4.5 and RCP8.5). Surface temperatures were projected to increase by 0.18 K yr −1 and 0.34 K yr −1 under RCP4.5 and RCP8.5, respectively. Such increases in future surface temperatures will increase BVOC emissions, as emissions of isoprene and monoterpene (accounting for 77.73% of all BVOCs in China at the current time) are projected to increase by 11.13% and 25.20% under the two RCP scenarios in the 2050s, respectively. Consequently, such increases in BVOCs will also have considerable impacts on concentrations of O3 and SOA. BVOCs contribute 10.11% of O3 and 62.59% of SOA concentrations in eastern China at current time. Under the RCP8.5 scenario, climate-driven BVOC changes will enhance O3 and SOA concentrations by 0.90% and 7.33% in eastern China from current to the 2050s and account for 31.83% and 52.80% of total O3 and SOA changes, respectively, on average across five typical regions. Such increases in O3 and SOA concentrations resulting from climate-driven BVOC changes decline considerably under the RCP4.5 scenario to less than 0.80% and 6.50%, respectively, implying that climate mitigation can facilitate air pollution control by alleviating an increase in BVOCs. Highlights: BVOCs contribute 10.11% of O3 and 62.59% of SOA concentrations in eastern China. Considerable BVOC impacts are observed in regions with high anthropogenic emissions. BVOC emissions in China are projected to increase by 24.17% in the 2050s. Climate-driven BVOCs is a non-negligible pathway which impacts air quality. Mitigating climate change can reduce the increase in BVOC-contributed O3 and SOA.